(3ahGFO GdoefJbi dRhGFO GdHjgbjs - (3CMeO Hf CHi HcQ Hf YHO GdQMef Hf ESeGYjd Hf Sdje GdcfGfi GdHhUjQi, TgGH GdOjf CHh GdYHGS,J (B840 (3g` s
(3ChdgG (B:s
(3HGH (B: (3ef bGd jLhR WdGb GdScQGf hYJbg s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B175s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B91 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMOjK h GdeUWdMs